Integration of metagenomic and metabolomic insights into the effects of microcystin-LR on intestinal microbiota of Litopenaeus vannamei - Duan, Yafei; Xing, Yifu; Zeng, Shimin; Dan, Xueming; Mo, Zequan; Zhang, Jiasong; Li, Yanwei (Frontiers in Microbiology, 2022)
Microcystin-LR (MC-LR) is a hazardous substance that threaten the health of aquatic animals. Intestinal microbes and their metabolites can interact with hosts to influence physiological homeostasis. In this study, the shrimp Litopenaeus vannamei were exposed to 1.0 µg/L MC-LR for 72 h, and the toxic effects of MC-LR on the intestinal microbial metagenomic and metabolomic responses of the shrimp were investigated. The results showed that MC-LR stress altered the gene functions of intestinal microbial, including ABC transporter, sulfur metabolism and riboflavin (VB2) metabolism, and induced a significant increase of eight carbohydrate metabolism enzymes. Alternatively, intestinal metabolic phenotypes were also altered, especially ABC transporters, protein digestion and absorption, and the biosynthesis and metabolism of amino acid. Furthermore, based on the integration of intestinal microbial metagenomic and metabolome, four bacteria species (Demequina globuliformis, Demequina sp NBRC 110055, Sphingomonas taxi and Sphingomonas sp RIT328) and three metabolites (yangonin, α-hederin and soyasaponin ii) biomarkers were identified. Overall, our study provides new insights into the effects of MC-LR on the intestinal microbial functions of L. vannamei.